Climate regulates alpine lake ice cover phenology and aquatic ecosystem structure - Daniel L. Preston; Nel Caine; Diane M. McKnight; Mark W. Williams; Katherina Hell; Matthew P. Miller; Sarah J. Hart; Pieter T. J. Johnson (Geophysical Research Letters)
Abstract High‐elevation aquatic ecosystems are highly vulnerable to climate change, yet relatively few records are available to characterize shifts in ecosystem structure or their underlying mechanisms. Using a long‐term data set on seven alpine lakes (3126 to 3620 m) in Colorado, USA, we show that ice‐off dates have shifted 7 days earlier over the past 33 years and that spring weather conditions—especially snowfall—drive yearly variation in ice‐off timing. In the most well studied lake, earlier ice‐off associated with increases in water residence times, thermal stratification, ion concentrations, dissolved nitrogen, pH, and chlorophyll a. Mechanistically, low spring snowfall and warm temperatures reduce summer stream flow (increasing lake residence times) but enhance melting of glacial and permafrost ice (increasing lake solute inputs). The observed links among hydrological, chemical, and biological responses to climate factors highlight the potential for major shifts in the functioning of alpine lakes due to forecasted climate change.